A Socio-political Analysis work of John Stuart Mill’s Theory of Liberty and his Utilitarian Premises - Aziz, Mahir Abdulwahid (Zanco Journal of Human Sciences, 2021)
This theoretical study deals with the most influential British philosopher of the nineteenth century, namely John Stuart Mill (1806 – 1873). The study offers a socio-political interpretation of Mill’s views on Liberty and Utilitarian Premises in a descriptive way. The objective of this study is to elaborate and discuss his major contribution in the field of liberal theory by focusing on his very well-known book On Liberty published in 1859. The aim of the study however, is to problematize the main points in which Mill focused in his philosophical argument on liberal thinking and liberty. The main argument of this study is that there is a clear inconsistency between Mill's theory of Liberty and his Utilitarian premises. In doing so, the study is divided into eight sections. Section one is devoted to the introduction. Section two shows the objectives of the study and the method in which applied. Section three raises the major questions in which the study tries to answer. Section four briefly assesses Mill’s relationship to Jeremy Bentham. Section five analyses Mill’s very famous work, On Liberty. Section six focuses on Mill’s views on liberalism and humanism. Section seven discusses Mill’s Utilitarianism, individuality and the inconsistencies in his theory of liberty. Section eight demonstrates the conclusion in a critical assessment. The objectives of this theoretical study are: firstly, to elaborate and discuss his major contribution in the field of liberal theory by focusing on his very well-known book On Liberty published in 1859, secondly, to problematize the main points in which Mill focused in his philosophical arguments on liberal thinking and liberty. On Liberty is well known as one of great classic texts in modern political theory. Methodologically, the study lies at the intersection of sociology, political science, and liberty theory. It should be emphasised that this study has been done according to a historical and an explanatory approach method, which applied in both fields of political theory and political sociology. The explanatory approach is a method to make us understand something by describing and illustrating. Its intents merely to explore the research questions and does not offer final and conclusive solutions to the exciting questions. Therefore, this study uses the literature research and text analysis as a tool for it.